Maternal and fetal adropin levels in gestational diabetes mellitus - Celik, Ebru; Yilmaz, Ercan; Celik, Onder; Ulas, Mustafa; Turkcuoglu, Ilgin; Karaer, Abdullah; Aydin, Suleyman (Walter de Gruyter Gmbh, 2013)
Aim: To evaluate maternal and cord blood serum adropin concentrations in pregnant women with gestational diabetes mellitus (GDM). Study design: Twenty pregnant women with GDM and 20 gestational age-matched healthy pregnant women participated in the study. Maternal serum and cord blood adropin levels were assessed using an enzyme immunosorbent assay, at the time of birth. The relation of maternal serum and cord blood adropin levels with metabolic parameters were also assessed. Results: The mean maternal and cord serum adropin in the GDM group were significantly lower than those of the control women (P = 0.01 and P<0.001, respectively). Maternal serum adropin levels did not correlate with either fetal serum adropin levels or maternal metabolic values. Conclusion: The data suggest that low adropin levels may contribute to the underlying pathogenesis of GDM.
Keywords: Adropin; cord blood; gestational diabetes mellitus; glucose; homeostasis model of assessment - insulin resistance (HOMA-IR)